Roadmap on Neuromorphic Photonics - Brunner, Daniel; Shastri, B.; Qadasi, Mohammed A. Al; Ballani, Hitesh; Barbay, Sylvain; Biasi, S.; Bienstman, P.; Bilodeau, Simon; Bogaerts, Wim; Bohm, Fabian; Brennan, Grace; Buckley, Sonia M.; et al. (ArXiv, 2025)
This roadmap consolidates recent advances while exploring emerging applications, reflecting the remarkable diversity of hardware platforms, neuromorphic concepts, and implementation philosophies reported in the field. It emphasizes the critical role of cross-disciplinary collaboration in this rapidly evolving field.